Burnout and coping perceptions of volleyball players throughout an annual sport season - Alvarez Pires, D.; Ugrinowitsch, H. (Journal of Human Kinetics, 2021)
Burnout is a psychological syndrome of reaction to chronic stress that occurs in athletes who feel exhausted by a sport activity that was previously pleasurable and enjoyable. One technique to prevent and control the syndrome is through coping, which is the ability to deal with stressful situations. In contrast to traditional cross-sectiona approaches, this study aimed to investigate burnout and coping strategy characteristics over time and to analyze the relationship between burnout di mensions and coping strategies. Fifty-four high-level volleyball athletes (twenty-eight men and twenty-six women, age M = 25.57, SD = 4.72, range 18-35) completed paper-and-pencil measures of burnout and coping four times throughout a sport season. The Friedman test presented a significant increase in the reduced sense of athletic accomplishment (X2 = 20.58; p < 0.01) and sport devaluation (X2 = 19.83; p < 0.01) perceptions during the season. However, no coping differences were observed through the longitudinal analysis. Burnout dimensions showed a moderate inverse correlation to confidence/motivation at all measurement points during the season. Overall, the findings suggest that burnout perceptions increase as the season progresses, highlighting the relevance for the periodization of burnout prevention and control.